Pengaruh Pendidikan Kesehatan tentang Imunisasi Rubella terhadap Tingkat Pengetahuan Orang Tua di TK Perwanida 2 Palangka Raya: The Effect of Health Education on Rubella Immunization on Parents Knowledge Level in Perwanida 2 Kindergarten Palangka Raya - Indriani Indriani; Lensi Natalia Tambunan; Wenna Araya; Eko Saputra (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Background: Rubella is an infectious disease transmitted through the airways caused by the Measles and Rubella viruses. In Indonesia in 2017, rubella suspects of 5.77 per 100,000 population increased compared to 2016, which amounted to 5.0 per 100,000. Writing Purpose: To analyze the effect of health education on rubella immunization on the level of parental knowledge in Perwanida 2 Palangka Raya Kindergarten. Research Methods: Pre-experimental research. The research design used was Wilcoxon. From a population of 30 parents using a total sampling technique. Research Results: The results of the statistical analysis test with the Wilcoxson test obtained a p-value = 0,000 with a degree of significance α = 0.05. 0,000 <0.05, then H1 is accepted, which means it shows the influence of rubella immunization health education on the level of parental knowledge. Conclusion: There is an influence of health education on the level of parental knowledge. Every parent plays an important role in the child's health, especially by providing decent health insurance and immunizations to children.